(3GdYdGL HGdaUOs - (3bSWG Hf dhbG GdHYdHcj,J (B300 (3g` s
(3ChdgG (B:s
(3bGd bSW Hf dhbG(B: (3ELgGO GdfaS ai GdhaGA HGdaQGFV ChLH ef LgdgG ai GdfhGad aCdaJ dc CYRc Gddg cJGHkG , LeYJ ajg eG PcQ LGdjfhS ef GdYdGL HGdaUO hPdc dcKQI YdGLc Hg s
(3BNQgG (B:s
(3hgh OSe LOkG jDcd HGdYSd EPG cGf QWHkG, hHGdJeQ hGdOHS, hEPG cGf GdLHf aj jHSg EdG Gf WYeg ZjQ WYeg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B74 - (3U(B94s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B131s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B157 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs